Hastag SAVETHECOAST Tagger dalam Rangka Mangrove Sedunia di Kelurahan Maridan - Alamsyah, Alamsyah; Kurniawan, Diah Citra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2024)
Abstrak: Mangrove forests play a crucial role in the context of international relations, particularly concerning global environmental issues such as climate change, biodiversity conservation, and natural resource management. In Maridan Sub-district, Penajam Paser Utara, the mangrove ecosystem holds significant ecological value as a coastal protector, carbon absorber, and habitat for various species. However, its existence faces serious threats due to infrastructure development and environmental changes. To address these challenges, the authors conducted a mangrove planting and awareness campaign with the hashtag #SaveTheCoast. The event involved representatives from the local community, government institutions, and high school students as an initial step toward mangrove preservation and environmental consciousness. This effort is crucial as Maridan Sub-district is slated to be part of the National Capital (IKN), necessitating land expansion that could endanger the mangrove ecosystem. The activity reflects the cooperation between the local community, regional government, and educational institutions in safeguarding and preserving mangroves as a precious natural treasure. Through education, conservation, and shared awareness, it is hoped that the mangrove forests in Maridan Sub-district will continue to thrive for future generations while promoting sustainable coastal preservation and ecosystem management.